If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 4x = 10 + -2(-9x + -8) Reorder the terms: 5(-2 + x) + 4x = 10 + -2(-9x + -8) (-2 * 5 + x * 5) + 4x = 10 + -2(-9x + -8) (-10 + 5x) + 4x = 10 + -2(-9x + -8) Combine like terms: 5x + 4x = 9x -10 + 9x = 10 + -2(-9x + -8) Reorder the terms: -10 + 9x = 10 + -2(-8 + -9x) -10 + 9x = 10 + (-8 * -2 + -9x * -2) -10 + 9x = 10 + (16 + 18x) Combine like terms: 10 + 16 = 26 -10 + 9x = 26 + 18x Solving -10 + 9x = 26 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -10 + 9x + -18x = 26 + 18x + -18x Combine like terms: 9x + -18x = -9x -10 + -9x = 26 + 18x + -18x Combine like terms: 18x + -18x = 0 -10 + -9x = 26 + 0 -10 + -9x = 26 Add '10' to each side of the equation. -10 + 10 + -9x = 26 + 10 Combine like terms: -10 + 10 = 0 0 + -9x = 26 + 10 -9x = 26 + 10 Combine like terms: 26 + 10 = 36 -9x = 36 Divide each side by '-9'. x = -4 Simplifying x = -4
| 4*4X=49 | | x^2+7x-175=0 | | 2a-a-13=2 | | 0.2x=-26 | | 7d^2+5d+13=0 | | 3Y+7=49 | | -7(x+3)-10=14+4 | | 13y=12(y+6) | | 900=3n+3 | | 14+7x=91 | | 6x-11=67 | | (2x+3y)-5=6x-8y | | -8n+4(1+5n)=-6n+4 | | 9y=6y+12 | | 4(x-9)=-26 | | 4/x-5=-18/x+6 | | 2(a+9)=36.4 | | -4y+10x=36 | | 3x+2/x-1=8 | | 16.2=7c-9 | | 5x+8/2=14 | | 6e-2=17.8 | | 40x=60 | | 12(k+4)=60 | | -8+p=31 | | 2(x-5)+4=2x+3 | | 2.5=s/7 | | 5y-9+y+33=7y+30-4y | | 3x+1.7=9.2 | | -4/15=x-7/12 | | 5/8=y+1/8 | | a+6.6=4.9 |